Numerical simulation on influence of initial pressures on gas explosion propagation characteristics in roadway - Haohao, Zhang; Zhenzhen, Jia; Qing, Ye; Yu, Cheng; Shujuan, Li (Frontiers in Energy Research, 2022)
In order to investigate the influence of initial pressure on gas explosion propagation characteristics in roadway, the physical model of gas explosion with different initial pressures in roadway was established by the fluid-structure interaction algorithm of finite element analysis software ANSYS/LS-DYNA. The pressure of shock wave, the rise rate of the pressure and the flame propagation velocity were analyzed when the initial pressure was 0.08, 0.09, 0.10, 0.11, and 0.12 MPa, respectively. The results reveal that the maximum pressure of shock wave at the same position in the roadway increased significantly with the increase of initial pressure, which presented a quadratic function relationship. The time to reach the maximum pressure of shock wave was extended comparatively. In addition, the maximum rise rate of shock wave pressure increased with the increase of the initial pressure, which meant that the explosion hazard increased. The flame propagation velocity in roadway decreased linearly with the increase of initial pressure, and the flame propagation velocity decreased by 2.6% for every initial pressure increase of 0.01 MPa.